2008
DOI: 10.1128/cvi.00335-07
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protein Shedding on Detection of Mycobacterium avium subsp. paratuberculosis by a Whole-Cell Immunoassay Incorporating Surface-Enhanced Raman Scattering

Abstract: Mycobacterium avium subsp. paratuberculosis is responsible for extensive losses in dairy production on a global scale (44). M. avium subsp. paratuberculosis is also found in other domestic ruminants (e.g., sheep [30,34] and goats [45,46]) and wildlife (e.g., deer [21,31,32], antelope [6,17], bison [52], and rabbits [4,5,26]). Animals that are afflicted with M. avium subsp. paratuberculosis progress from silent infection to a subclinical phase with no observable symptoms. Low levels of shedding during this time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…It is difficult to extrapolate these results to the single-cell level for mycoplasmas, which tend to clump and for which CFU and plating efficiency are poorly defined [3] . Furthermore, we also cannot rule out the possibility that intact cells are not essential, and the ability to detect M. pneumoniae spectra may fall below the single-cell level due to recognition by SERS of cell components in cell lysates, as was reported recently for mycobacteria [41] .…”
Section: Resultsmentioning
confidence: 83%
“…It is difficult to extrapolate these results to the single-cell level for mycoplasmas, which tend to clump and for which CFU and plating efficiency are poorly defined [3] . Furthermore, we also cannot rule out the possibility that intact cells are not essential, and the ability to detect M. pneumoniae spectra may fall below the single-cell level due to recognition by SERS of cell components in cell lysates, as was reported recently for mycobacteria [41] .…”
Section: Resultsmentioning
confidence: 83%
“…paratuberculosis 35,36 ), and small molecules (i.e., a Vitamin D metabolite). 37 This paper describes the development of SERS-based sandwich immunoassays for the detection of MUC4 and CA19-9 and their application to the first ever measurement of MUC4 in patient sera.…”
mentioning
confidence: 99%
“…While it has previously been indicated that MMP contains a 30 amino acid hydrophobic domain near the C-terminal end suggestive of a membrane protein, the protein lacks a discernible N-terminal signal sequence (Bannantine et al, 2003 ). Moreover, it has already been experimentally demonstrated that MMP is both surface exposed and actively shed from live MAP bacilli (Yakes et al, 2008 ), suggesting that MMP is translocated in a non-classical manner similar to other mycobacterial proteins (Pallen, 2002 ; Bendtsen et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%